Progress of Recycling in the Built Environment Final report of the RILEM Technical Committee 217-PRE - Vázquez, Enric (RILEM State-of-the-Art Reports, 2013)
This report is a useful tool for countries starting to recycle aggregates or construction and demolition waste. It contains the latest developments in this field, introduces a completely new approach to the procedure of proportioning concrete mixtures with recycled aggregate, references recent publications, opinions and discrepancies in relation to the durability of recycled concrete, such as freeze-thaw standards, studies of chloride penetration and diffusion, and sulfate attacks, the use of the fine fraction <4mm, quality assurance of concrete recycled aggregate, sustainability and recycling construction waste and global impact assessment of urban renewal based on sustainable recycling strategies for construction and demolition waste. This volume will be of interest to recyclers, researchers and consumers.